SYSTEMS GENRES IN MODERN TRANSCARPATHIAN PRESS (based on publications “Transcarpathian truth” and “Old castle”) - Vashchuk, I. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the genre palette Carpathian periodicals, as well as the transformation of genres oldest newspaper in the land of " Transcarpathian Pravda" newspaper and "Old Castle" .